Electives as a Pedagogical Strategy for Fostering Medical Student Engagement and Exploration beyond the Standard Medical Curriculum - Dias, N.W.G.L.T.L.; Karunathilake, I.M.; Hettiarachchi, D.; De Abrew, A.; Amarasiri, M.M.P.L. (South-East Asian Journal of Medical Education, 2024)
Revamping a medical curriculum at a pace parallel to the development of medicine is an unattainable goal. Academic institutions ...
Keywords: Medical Students; Medical Curriculum